Community-Scale Surveillance of SARS-CoV-2 and Influenza A Viruses in Wild Mammals, United States, 2022–2023 - Grete Wilson-Henjum; J. Jeffrey Root; Alex Worgo; Jeffrey Chandler; Robin Dyer; Jeff Flores; Jesse Morris; Ian Plummer; John Paul Seman; Kyle Van Why; Caleb Wellman; H. Bryant White; et al. (Emerging Infectious Diseases)
Sampling of mammal communities across the United States during 2022–2023 detected evidence of SARS-CoV-2 antibodies in 3 new species and 2 previously described species and evidence of influenza A antibodies in 2 previously described species. Our analysis provides surveillance and sampling guidance for detection of rare exposure events.